116k views
3 votes
Find the simplified form of the expression. Give your answer in scientific notation. (5 x 10-6)(1 x 10-3)

User Manette
by
7.0k points

1 Answer

3 votes

Answer:


5*10^(-9)

Step-by-step explanation:

Given the expression:


\mleft(5*10^(-6)\mright)\mleft(1*10^(-3)\mright)​

First, open the brackets:


=5*10^(-6)*1*10^(-3)

Next, rearrange to bring like terms together:


\begin{gathered} =5*1*10^(-6)*10^(-3) \\ =5*10^(-6)*10^(-3) \end{gathered}

Finally, combine the powers of 10 using the addition law of indices:


\begin{gathered} =5*10^(-6+(-3)) \\ =5*10^(-6-3) \\ =5*10^(-9)\text{ (in scientific notation)} \end{gathered}

User Maheshwar Ligade
by
6.9k points